The effects of ultrafine palm oil fuel ash (UPOFA) towards mechanical properties of cement mortar - Sharifah Syazwani , Sayed Hashim (2014)
In general, with the production of palm oil to cater for the demand of the industry, the palm oil factory itself generates an amount of waste from its production which considered as waste solids. Usage of palm oil fuel ash (POFA) is uncontrollable and minimal which contribute to solid waste in landfills that caused environmental problem. HoWever, the growing problem of waste materials can be reduced if new recycling methods can be found for the wastage of palm oil. It has been shown that addition of pozzolan admixtures such as palm oil fuel ash and fly ash with suitable volume level can improve the strength and permeability of concrete. It was also found that using such waste materials result in positive effects on properties of Portland cement mortar and concrete. This paper presents the effects of ultrafine palm oil fuel ash(POFA) towards mechanical properties of mortar in different replacement level and compared with control mixture. In order to improve its properties, the POFA was ground until the average particle size reducedto 5.91 pm. Then, it was used to replace ordinary Portland cement (OPC) by weights of 0%, 10%, 20% and 30% in order to improve the mechanical properties and interfacial zone microstructure of mortar. It was found that mortar containing ultrafine POFA replacement between 10% and 20% can improve the workability, compressive strength, flexural strength, porosity, water, absorption and modulus of elasticity. In addition, cement replacement by 20% of ultrafine POFA gave the highest compressive strength. The results, therefore, suggest that POFA with high fineness is suitable to use as cement replacement in improving the mechanical properties and microstructure of mortar.